Impact of Macroeconomic Variables on the Performance of Nepalese Financial Institutions - Prem Bahadur Budhathoki; Shiva Raj Ghimire; Ashok Basnet (Interdisciplinary Journal of Management and Social Sciences, 2024)
The macroeconomic variables—interest rate, inflation rate, unemployment rate, and economic growth—can influence the performance of financial institutions. Hence, this study examines the impact of macroeconomic variables on the performance of Nepalese financial institutions. The study employed descriptive, correlation, and causal-comparative research designs. The dataset of 10 commercial banks covering 2013/14 to 2022/23 is used. Descriptive statistics, Pearson’s correlation, and multiple regression models are used to investigate the influence of predictor variables on response variables. The study’s findings revealed that the gross domestic product (GDP) growth rate has an insignificant negative impact on the performance of Nepalese commercial banks. Similarly, inflation, interest, and unemployment rates negatively and statistically significantly impact banks’ performance. To develop a sustainable financial system, policymakers can use these findings to reduce interest, inflation, and unemployment rates.